Nanoporous Quantum Filters: Inside Vapor-Liquid Transitions of Quantum Fluids inNanopores - Kowalczyk, Poitr; Gauden, P.; Terzyk, A. (American Chemical Society, 2010)
We study the impact of quantum fluctuations on the phase diagram of a realistic quantum liquid, namely, neon confined in atomistic carbon nanopores at 35 K. Due to the action of attractive solid-fluid potential, both classical and quantum neon vapor condense at lower pressures in carbonaceous nanopores than bulk neon. However, we found that continuous van der Waals s-shaped isotherms, which include stable, metastable, and unstable states computed from classical simulations, are shifted to lower values of pressures in comparison to those from path integral calculations. This systematic underestimation of equilibrium vapor-liquid transition pressures as well as spinodals in classical simulations is caused by neglecting the zero-point motion of adsorbed neon at 35 K. Delocalized neon atoms excluded more volume in the adsorbed phase than the classical neon particles. Thus, adsorbed and compressed liquidlike phases of quantum neon in the studied nanopores are characterized by lower densities than their classical counterparts. Interestingly, equilibrium vapor-liquidtransition pressures of confined neon at 35 K computed from classical simulations are shifted to lower values in comparison to those computed from quantum simulations by ˜30% for different pore sizes. Simulations of classical neon at higher effective temperatures reveal that liquidlike phases of confined quantum neon at 35 K look like classical ones at higher effective temperature of 37 K. Our calculations clearly show that quantum fluctuations cannot be neglected in calculations of phase transitions of quantum fluids at cryogenic temperatures.